Incorporating 'reason for use' into the prescribing process of medication: a survey on the opinion of patients in Flanders, Belgium - Marijke Peeters; Elias Iturrospe; Dominique Jans; Alexander L. N. van Nuijs; Hans De Loof (BMC, 2022)
Abstract Background A longstanding debate exists about including a 'reason for use' on prescriptions for medication. Little is known, however, about patients' opinions on this subject. Methods An internet-based questionnaire, consisting mainly of Likert scale questions, was distributed online to the general public in Belgium. Results from 1034 responses were analyzed using descriptive statistics. Results Opinions from patients toward including a 'reason for use' on medication prescriptions were generally positive. A clear majority of 62% increased to 74% after providing information about the possible link between indication and medication dose. A majority of the participants expressed a positive attitude regardless of the pathology involved, although sexually transmitted diseases were of greatest concern. Other important aspects differentiating the opinion positively was the transmission of this information in an electronic-only form and limiting it to the regular pharmacist excluding further use by third parties such as other pharmacies or insurance companies. Patients using multiple medicines and those frequenting the same pharmacy also had a more favorable opinion about including the reason for use. In addition, analysis of physician and pharmacist questionnaire responses, explicitly excluded from the main analysis, confirmed the known contrasting opinions in these subgroups. Conclusions Patients have strong support for transferring information on the 'reason for use' of their prescriptions to their regular pharmacy if this is done in a secure and privacy-conscious way enabling increased patient safety and improved pharmaceutical care.